2018
DOI: 10.1080/21870764.2018.1533444
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of dihydroxyacetone from glycerol over a Pt/CeO2-ZrO2-Bi2O3/SBA-16 catalyst

Abstract: A Pt/CeO 2-ZrO 2-Bi 2 O 3 /SBA-16 catalyst was prepared to realize highly selective oxidation of glycerol to produce dihydroxyacetone (DHA). An active oxygen supply from the CeO 2-ZrO 2-Bi 2 O 3 promoter effectively oxidized glycerol to produce DHA under moderate conditions (i.e. at 30°C without applied pressure). After a 4 h catalytic reaction using the Pt/CeO 2-ZrO 2-Bi 2 O 3 / SBA-16 catalyst, the DHA yield and selectivity rose to 76% and 84%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Furthermore, the DHA selectivity was obviously improved. These increases might be attributed to both an increase in the oxygen storage abilities and the introduction of the Bi 3+ ions, much as in our previous study [15]. The excess Bi 3+ introduction (x = 0.20) in Pt/CZBi(x)/SBA caused a decrease in DHA selectivity, while the glycerol conversion was still increased, suggesting that DHA was further oxidized.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, the DHA selectivity was obviously improved. These increases might be attributed to both an increase in the oxygen storage abilities and the introduction of the Bi 3+ ions, much as in our previous study [15]. The excess Bi 3+ introduction (x = 0.20) in Pt/CZBi(x)/SBA caused a decrease in DHA selectivity, while the glycerol conversion was still increased, suggesting that DHA was further oxidized.…”
Section: Resultssupporting
confidence: 65%
“…By inserting the CeO 2 -ZrO 2 -Bi 2 O 3 promoter and a Pt activator into the pores of mesoporous silica SBA-16 (Santa Barbara Amorphous No. 16) with a large surface area, we demonstrated that Pt/CeO 2 -ZrO 2 -Bi 2 O 3 /SBA-16 effectively converted glycerol to DHA [15]. This high efficiency is considered to be affected by the oxygen supply from the promoter and by geometric effects among glycerol, Pt, and surface Bi 3+ ions in the promoter.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…There is thus an increasing surplus of glycerol, creating a need to develop alternative ways to use residual glycerol. 2 Due to its high functionalization, glycerol can be transformed into several value-added products ( Table 1), such as lactic acid, [3][4][5] glyceric acid, 6-8 glycolic acid, [9][10][11] oxalic acid, 9,12 dihydroxyacetone, [13][14][15] glyceraldehyde, [16][17][18] 1,2-propanediol, [19][20][21] 1,3-propanediol, 22-24 1-propanol, 25,26 acrylic acid, [27][28][29] acrolein, [30][31][32] syngas, [33][34][35] mono-, di-, tri-glycerides, [36][37][38] triacetin, [39][40][41] glycerol oligomers, 42,43 and polymers. 44 Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry 45,46 as raw material for the production of pharmaceuticals, 47 cosmetics, 48 textiles, 49 leather,…”
Section: Reactionmentioning
confidence: 99%
“…Due to its high functionalization, glycerol can be transformed into several value‐added products (Table ), such as lactic acid, glyceric acid, glycolic acid, oxalic acid, dihydroxyacetone, glyceraldehyde, 1,2‐propanediol, 1,3‐propanediol, 1‐propanol, acrylic acid, acrolein, syngas, mono‐, di‐, tri‐glycerides, triacetin, glycerol oligomers, and polymers . Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry as raw material for the production of pharmaceuticals, cosmetics, textiles, leather, and, in a fast‐growing niche market, as monomer for the biodegradable polymer poly‐(lactic acid) or PLA .…”
Section: Introductionmentioning
confidence: 99%